The emergence of entrepreneurial economics - Vinig, G. T.; Voort, R. C. W. van der (Research on technological innovation, management and policy, 2005)
Provides insights on the theory of entrepreneurship in the economy and research on entrepreneurship. This book contributes to the emergence of the Entrepreneurial Economics field, in which, the study of patterns in the complex, seemingly chaotic and unpredictable process of entrepreneurship and its role in the economy stands central.